Detection of Beta-Agonist Residues in Meat Using Enzyme Linked Immunosorbent Assay and Gas Chromatography Mass Spectrometry - S. Ponniah, P. Jeyaletchumi (2003)
The prevalence, type and concentration of beta-agonist residues in the liver and meat of three types of livestock animals i.e. goats, cattle and swine were studied using Gas Chromatography-Mass Spectrometry. Beta-agonist residues were only detected in swine with a prevalence of 16.6% in meat and 20% in liver sampled. The concentration of beta-agonist residues in the positive samples ranged between 1ng/g to 9ng/g. The performance of the multi-residue analysis method used was assessed through recovery studies and found to be varied among the beta-agonists wherein terbutaline showed the highest recovery values (78-83%) whereas salbutamol showed the lowest recovery values (22% -31%). The coefficient of variation (C.V.) had values between 1-12% which indicate acceptable variation for the method.